Roads and water: interactions considered on different levels of planning and designing - Dąbal, Agata (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The main subject of this paper is the relationship between roads and one of the environmental components: water. This element was chosen due to its common occurrence and the necessity for all the organisms. Additionally because of its destroying force. Analyses were conducted on different levels of planning and designing, from strategic documents to individual cases. The study showed that strategic documents prepared for water management are really important for designing, construction and exploitation of roads. Nowadays, a modern attitude towards designing elements which can have an impact on the water bodies is necessary. This approach needs to take into consideration environmental objectives stated for water bodies in order to reduce pressure, not only implied by sewage precipitation water which changes river water quantity and quality, but also has an impact on the river bed which can influence hydrodynamic balance. This modern attitude should encompass the issue of preservation river bed characteristic status as described by typical water bodies reference conditions.